Pemberdayaan Pamsimas dengan Digitilisasi sistem berbasis website dan Arduino - Achmad Vandian Nur; Fenilinas Adi Artanto; Khusna Santika Rahmasari (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
The increasing speed of information accessibility marked by the birth of digital technology has changed the way we live our daily lives. Skills in this technological field can help us overcome various challenges in the digital era. Of the many skills in the field of technology and information today, the ability and mastery of the Internet of Things (IoT) is one of the most important areas. One key aspect of being able to understand Internet of Things technology is its utilization for communities in need. This Community Service Activity is in the form of community empowerment with the theme "Empowering Pamsimas (Community-Based Drinking Water and Sanitation Program) Banyu Berkah Setono using IoT". This activity aims to empower Pamsimas, which is still based on written data, to become digital-based data through a website. The implementation of this activity was carried out by conducting initial observations and coordinating with the head of Pamsimas Banyu Berkah as a partner of this activity, followed by the implementation stage of training activities. The implementation method is providing material about the website, as well as how to fill in and practice using the website itself. From this training activity, participants were able to understand the basic concepts of website organization, and were also able to input Pamsimas customer data on the website.